2016
DOI: 10.2139/ssrn.2796600
|View full text |Cite
|
Sign up to set email alerts
|

Competition, Efficiency, and Soundness in European Life Insurance Markets

Abstract: This paper provides cross-country evidence on the association between soundness and competition in the life insurance industry where competition is measured by the Boone indicator. We analyze 10 European Union (EU) life insurance markets over the postderegulation period 1999-2011. The results indicate that competition increases the soundness of the EU life insurance markets but incentivizes EU life insurers to hold less capital. Since the Boone indicator measures competition based on the reallocation of profit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 52 publications
4
51
1
Order By: Relevance
“…In this study, we also consider the decision on the level of assets under management in order to analyze the efficiency of insurers’ accounts receivable management and its effect on profitability (see Cummins et al., 2017). We would expect a positive relationship between this ratio and insurers’ profitability.…”
Section: Background and Literature Review On Firm Decision Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we also consider the decision on the level of assets under management in order to analyze the efficiency of insurers’ accounts receivable management and its effect on profitability (see Cummins et al., 2017). We would expect a positive relationship between this ratio and insurers’ profitability.…”
Section: Background and Literature Review On Firm Decision Variablesmentioning
confidence: 99%
“…The minimum regulatory solvency of every insurer over the analyzed sample period is calculated based on its activities and the insurer's solvency margin includes the insurer's net worth free of any expected commitments minus illiquid assets. Reinsurance utilization is calculated as the ratio of ceded premiums to direct premiums plus reinsurance premiums assumed (see e.g., Weiss and Choi, 2008). The leverage variable that we use in the analysis is defined as debt financial capital to total assets. We use the ratio of invested assets to total assets to control for the efficiency of insurers’ accounts receivable management (see Cummins et al., 2017). Following Cummins and Nini (2002), we include the premiums growth variable, defined as ((premiums at time t /premiums at time t −1) −1). The corporate diversification variable is constructed by the standard approach that is based on a Herfindahl concentration index of net premiums written across business lines (e.g., Mayers and Smith, 1994; Berry‐Stölzle et al., 2012; Biener et al., 2016).…”
Section: Data Sources and Variable Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased competition between companies will make the company more driven to improve its services and improve efficiency [6]. This study, supported by Eling & Schaper [7], identified the impact of environmental changes on productivity and efficiency on European life insurance.…”
Section: A Hypothesismentioning
confidence: 92%
“…Strong competition has the potential to increase managerial pressure in reducing slackness and improving efficiency [5]. The study by Cummins, Rubio-Misas, Vencappa [6] stated that increased competition could make insurance companies change from being inefficient to efficient, hence, the company became healthier. Changes in the productivity environment had an impact on increasing the efficiency of insurance companies because the business environment became increasingly challenging [7].…”
Section: Introductionmentioning
confidence: 99%